A new stepwise and piecewise optimization approach for CO2 pipeline. (June 2016) - Zhao, Dongya; Tian, Qunhong; Li, Zhaomin; Zhu, Quanmin
Highlights: We propose a stepwise optimization to improve the optimal accuracy. We propose a piecewise optimization to deal with the seasonal temperature variance. We use numerical approach to validate the proposed approach. Abstract: The process of CO2 capture, transportation, enhanced oil recovery (EOR) and storage is one of the best ways for CO2 emission reduction, which is also named as Carbon Capture, Utilization and Storage (CCUS). It has been noted that CO2 transportation cost is an important component of the total investment of CCUS. In this paper, a novel stepwise and piecewise optimization is proposed for CO2 transportation design, which can compute the minimum transportation pipeline levelized cost under the effect of temperature variation. To develop the proposed approach, several models are referred to lay a foundation for the optimization design. The proposed optimal algorithm is validated by using numerical studies, which shows the approach can reduce the levelized cost and improve the optimization performance in comparison with the existing methods.